Speciation and Optimization of Multi-Elements Analysis of River Sediment in Shanghai by ICP-MS with Microwave-Assisted Digestion Method - Li, Yuanheng; Zhang, Daofang; Huang, Yuanxing; Yuan, Shijue; Xu, Zhihua (Asian Journal of Chemistry, 2015)
An analytical method was systematically developed for the multi-element analysis of Cr, Ni, Cu, Zn, Pb and Cd in sediments of Huangpu River in Shanghai by inductively coupled plasma mass spectrometry (ICP-MS) with microwave-assisted acid digestion. Three significant factors including drying method, digestion solution (volume ratio of HNO3: HF: H2O2) and the presence of centrifugal separation procedure were investigated individually and compared. Results showed that drying under the temperature of 50 °C caused the largest fluctuation in final results, whereas drying under 100 °C had the least variation in detection results. Increasing the ratio of HF or H2O2 was beneficial for fully digestion of sediment samples. Centrifugation of the digestion solution could obtain higher detected metal concentration. Speciation of the sediment showed that the largest fraction of metals existed was residual fraction, followed by Fe-Mn oxide fraction and organic matter fraction.